The Influence of Tourist Motivation on Intention to Attend the Seventeenth "Right Here" World Tour Jakarta 2025 Concert - Sandrina Wielda Adoe; Ety Dwi Susanti (LACULTOUR: Journal of Language and Cultural Tourism, 2026)
Concert attendance is no longer perceived merely as a form of entertainment but also as a type of event-based tourism influenced by tourists' travel motivations. This study aims to examine the effect of tourist motivation on visiting intention toward the Seventeen "Right Here" World Tour Jakarta 2025 concert. A quantitative approach was employed, involving 100 respondents who had attended the concert, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, validity and reliability tests, classical assumption tests, simple linear regression, the t-test, and the coefficient of determination using IBM SPSS Statistics. The findings reveal that tourist motivation has a positive and statistically significant effect on visiting intention. The higher the level of tourist motivation, the stronger the intention to attend the concert. Motivations driven by the desire for entertainment, social interaction, and emotional experiences were identified as the primary factors influencing visiting intention. These findings provide practical insights for concert organizers and tourism stakeholders in developing effective marketing strategies to enhance visitor interest and support the sustainable growth of event tourism.